Essential thrombocythemia with CALR mutation and recurrent stroke: two case reports and literature review. (April 2022) - Chen, Rong; Shi, Xiaodan; Wang, Luojun; Wang, Xuan; Wei, Jingya; Kang, Xiaogang; Du, Fang; Gao, Shan; Yang, Fang; Jiang, Wen
Cerebrovascular events, especially ischemic stroke, are common complications of essential thrombocythemia (ET). Compared to JAK2V617 F mutation, CALR mutation is considered as a lower risk factor of thrombosis in ET. Until now stroke in ET with CALR mutation has rarely been reported. We retrospectively investigated patients diagnosed with stroke and ET in Xijing hospital of Air Force Medical University, from 2015 to 2021. Clinical characteristics (including medical history, physical and auxiliary examination and prognosis) were recorded and associated literature was reviewed. Among the 19 patients diagnosed with both stroke and ET we retrieved, two cases were positive for CALR mutation. In case 1, a 71-year-old man developed the first ischemic event under the treatment of anagrelide, followed by a hemorrhagic stroke after receiving aspirin and clopidogrel for 4 months. Ischemic stroke reccurred and the neurological function deteriorated progressively. In case 2, a 44-year-old man presented with hypoxic-ischemic encephalopathy due to serious myocardial infarction and subsequent brain imaging indicated three times of ischemic stroke events. The patient gradually got improved through cytoreductive and antiplatelet therapy and rehabilitation. Literature review showed that cerebrovascular event is the most serious neurological complication of ET and may be the presenting symptom. Most of reported cases with ET accompanied by stroke were positive for JAK2 V617 F mutation, but with rare CALR mutation. ET with CALR mutation can cause both hemorrhagic and ischemic stroke. Identification of such rare causes of stroke is of great importance to provide precise and individualized prevention and therapy.